Teachers’ emotional exhaustion before and during the COVID-19 pandemic: Neither emotional exertion nor vacation feeling - Bleck, Victoria; Lipowsky, Frank (Frontiers in Psychology, 2022)
Purpose In this paper, we use latent change models to examine the changes in in-service teachers’ emotional exhaustion before and during the COVID-19 pandemic. As a result of the pandemic, teachers are confronted with challenging tasks, which can lead to stress and burnout. Resultingly, teachers’ stress experiences have been examined in different studies. However, often the change in those experiences remains unclear. Against this background, we investigate longitudinally how the emotional exhaustion of a cohort of German teachers changes. In addition, we examine whether gender, age, teaching degree studied, or the amount of time spent in distance learning affected the change during the pandemic. Methods We surveyed German veteran teachers (N = 382) about their emotional exhaustion at three measurement points. The first two surveys were before the COVID-19 pandemic (t1: winter 2016/2017; t2: spring: 2019), and the third measurement point was after the first lockdown Germany in summer 2020 (t3). To answer the research questions, we used neighbor-change models. Results Emotional exhaustion increased between the first two measurement points (t1, t2) but decreased in the following period (t2, t3). The changes in the two periods did not differ significantly from each other. Neither gender, age, nor the teaching profession studied influenced the change in emotional exhaustion. The hours spent in distance learning were also not a significant predictor. Conclusion In summary, the COVID-19 pandemic does not appear to be associated with higher emotional exhaustion across the veteran teachers. However, there are some teachers whose emotional exhaustion rises to high levels. Those teachers deserve special attention.